2020
DOI: 10.1017/s0022149x20000358
|View full text |Cite
|
Sign up to set email alerts
|

Helminths associated withNorops fuscoauratus(Squamata, Dactyloidae) in highland marshes of the Brazilian semi-arid

Abstract: Helminthological studies may contribute with valuable information on host biology and conservation. Herein, we provide new data on helminths infecting the lizard Norops fuscoauratus, testing one of the factors considered most important in parasitic ecology: host size. We analysed 25 specimens of N. fuscoauratus from three highland marshes in the Brazilian semi-arid. Eight taxa of helminths belonging to Nematoda, Trematoda and Acanthocephala were found. Physaloptera sp. showed the higher prevalence (40%), with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 66 publications
(90 reference statements)
1
2
0
Order By: Relevance
“…Norops fuscoauratus is appointed for second time intermediate host of Acanthocephala in Cystacanth phase (Santos Mesquita et al, 2020). In this study, these parasites were found in the body cavity and gastrointestinal organs and confirm the relationship between the site of infection in the host and the way of transmission of endoparasites.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Norops fuscoauratus is appointed for second time intermediate host of Acanthocephala in Cystacanth phase (Santos Mesquita et al, 2020). In this study, these parasites were found in the body cavity and gastrointestinal organs and confirm the relationship between the site of infection in the host and the way of transmission of endoparasites.…”
Section: Discussionsupporting
confidence: 73%
“…(D= 1) and Strongyluris oscari (D= 1). Already in anoles of Murici (AL), we obtained Brito et al (2014a, b), Araújo-Filho et al (2014) for the populations from the semi-arid; Cabral et al (2018), Amorim andÁvila (2019) andSantos Mesquita et al (2020) for humid forest ("Brejos-de-altitude") and Almeida-Gomes et al (2012), Barreto-Lima et al (2012) and Teixeira et al (2020) for lizards from the Atlantic Forest. In addition to these contributions, the descriptive study by Albuquerque et al (2012) should be highlighted.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…References: Travassos (1926) , Fabio (1982) in Campião et al (2014) , Vizcaíno (1993) , Torres & Puga (1996) , Azevedo-Ramos et al (1998) in Campião et al (2014) , Puga & Torres (1999) , Goldberg & Bursey (2003) , Iannacone (2003) , Duré et al (2004) , González & Hamann (2006) , Hamann et al (2006a , b ), Schaefer et al (2006) ; Smales (2007a , b ), Zaracho & Lamas (2008) , Hamann et al (2009) , Lamas & Lunaschi (2009) , Hamann et al (2010) , Santos & Amato (2010) , Hamann et al (2012) , Silva & Müller (2012) , Zaracho et al (2012) , Hamann et al (2013) ; Smales (2013) , Hamann et al (2014) , Graça et al (2017) , Martins-Sobrinho et al (2017) , Quirino et al (2018) , González et al (2019) , Dos Santos Mesquita et al (2020) , Aguiar et al (2021) in De Oliveira et al (2022) , Cuellar et al (2022) , Silveira et al (2022) , Coimbra et al (2023) , Prata et al (2023) and present study.…”
Section: Checklist Of Paratenic Hosts Of Centrorhynchus ...mentioning
confidence: 97%